2021
DOI: 10.1007/s10792-021-01774-5
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal thickness changes in children with chronic heart failure due to dilated cardiomyopathy

Abstract: Purpose To evaluate choroidal thickness (CTh) in children with chronic heart failure (CHF) secondary to dilated cardiomyopathy (DCM) using spectral domain optical coherence tomography (SD-OCT) and to compare their values to those of healthy children. Methods Sixty eyes of thirty children (mean age 9.9 ± 3.57 years) with chronic heart failure (left ventricular ejection fraction, LVEF ≤ 55%) due to DCM lasting for over 6 months were prospectively enrolled. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…They hypothesized that a low cardiac output might lead to vasoconstriction development in peripheral vessels like orbital and choroidal arteries to maintain critical organs’ blood supply, causing choroidal ischemia and retinal pigment epithelium atrophy. Rakusiewicz et al 21 discovered that children with congestive HF due to dilated cardiomyopathy had a thinner CT at all measured locations. They found that chronic HF impacted CT and that this parameter might be useful for monitoring the clinical progression of dilated cardiomyopathy in children.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…They hypothesized that a low cardiac output might lead to vasoconstriction development in peripheral vessels like orbital and choroidal arteries to maintain critical organs’ blood supply, causing choroidal ischemia and retinal pigment epithelium atrophy. Rakusiewicz et al 21 discovered that children with congestive HF due to dilated cardiomyopathy had a thinner CT at all measured locations. They found that chronic HF impacted CT and that this parameter might be useful for monitoring the clinical progression of dilated cardiomyopathy in children.…”
Section: Discussionmentioning
confidence: 96%
“…Relying solely on retinal vasculature as a biomarker can complicate the evaluation of patients with HF. On the other hand, the ability to examine the choroidal layers with swept source or EDI-OCT offers new research opportunities for patients with HFrEF and the ischemic type of HFrEF, which is the leading cause of LV dysfunction in adults worldwide [19][20][21][22] .…”
Section: Discussionmentioning
confidence: 99%